Carex yangchunensis, a new species of Cyperaceae from the limestone regions of Guangdong, South China - Yi-Fei Lu; De-Chang Meng; Xiao-Feng Jin (PhytoKeys)
Carex yangchunensis (Cyperaceae), a new species of Carex sect. Cryptostachyae in limestone regions of Guangdong, China, is described and illustrated. Both morphological observation and molecular analysis revealed that the new species was similar to C. cryptostachys, but differs in having inflorescence with 4–8 spikes, ovoid or nearly globose, 3–8 mm long, utricles (2.5–3.5 mm long) and nutlets (2–2.2 mm long) shorter, style base thickened, leaves narrower, 3–6 mm wide and culms 8–25 cm tall. Scanning electron micromorphology of utricles and nutlets of the new species and the related species C. cryptostachys are provided.